El juego como estrategia en el desarrollo de la motricidad gruesa en la Escuela de Educación Básica Paul Harris - Saraguro Mendieta, Jennifer Marina; Monserrate Cuenca, Jessica Roxana (Machala : Universidad Técnica de Machala, 2022)
The present research work deals with an integrative project, and focused on applying games to improve the development of gross motor skills in boys and girls, whose objective was to analyze the contribution of games as a strategy for the development of motor skills. thick in physical education classes with elementary basic education students from the Paul Harris school. The data collection was based on the qualitative approach, with a non-experimental and descriptive methodology, managing to diagnose the reality in the Paul Harris school. In relation to games and the development of gross motor skills. The methods with the greatest incidence in this investigation is the analytical-synthetic method and others that were integrated as auxiliaries, such as, the comparative and the bibliographic, which contributed significantly at the time of collecting the information based on the specific objectives to contribute to the general objective, which were written to cover aspects related to literary review, field research and finally to support the integrating proposal, as a contribution in favor of the educational institution that facilitated access to carry out the research. In relation to the sample, the teacher of the elementary sublevel was considered, since the number is two teachers, In addition, the director of the Lcda. campus was taken into account. Daysi Paladins. The selected instruments were the checklist and the guide of structured questions, which for its construction relates the objects of study, from where four dimensions were derived and consequently the indicators served as a guide for the preparation of the instruments, which facilitated the reception of opinions and attitudes of the people involved in this research work and at the same time score the range of values from fixed answers. The analysis of the results in the survey shows that games are applied to improve and develop gross motor skills correctly, specifying that teachers should be guided by educational videos, via the Internet, since they are not specialized in the area of education physical. For the above and responding to the third specific objective, the integrative proposal was defined, which was oriented to determine the orientation required by the teacher responsible for the subject of physical education to improve their performance in the application of games in contribution to the development of motor skills. gross. during physical education classes with elementary basic education students from the Paul Harris school as a contribution to the improvement of gross motor skills. The proposal was composed of four implementation phases addressed to a director and classroom teacher, in addition to logistical resources and feasibility assessment with the dimensions, technical, economic, social and environmental, demonstrating the ability to achieve the objectives of the project. proposal, determining the feasibility and material capacities of the executing parties of the proposal.
En relación con los juegos y el desarrollo de la motricidad gruesa. Los métodos de mayor incidencia en esta indagación es el método analítico-sintético y otros que se integraron en calidad de auxiliares, como, el comparativo y el bibliográfico, mismos que aportaron significativamente al momento de recabar la información con base a los objetivos específicos para contribuir al objetivo general, mismos que estuvieron redactados para abarcar aspectos relacionados con la revisión literaria, con la investigación de campo y finalmente para sostener la propuesta integradora, como aporte a favor de la institución educativa que facilitó el acceso para concretar la investigación. En relación con la muestra se consideró a la docente del subnivel elemental, puesto que el número es de una docente, además, se tomó en cuenta a la directora del plantel Lcda. Daysi Paladines. Los instrumentos seleccionados fueron lista de cotejo y la guía de preguntas estructuradas, que para su construcción se relaciona los objetos de estudio, de donde se derivaron cuatro dimensiones y en consecuencia los indicadores sirvieron de guía para la elaboración de los instrumentos, que facilitó la recepción de opiniones y actitudes de las personas involucradas en este trabajo de investigación y al mismo tiempo puntuar a partir de respuestas fijas el rango de valores. El análisis de resultados en la encuesta demuestra que, si se aplican juegos para poder mejorar y desarrollar de una manera correcta la motricidad gruesa, concretando que los docentes deben guiarse mediante videos educativos, vía internet, ya que ellos no están especializados dentro del área de educación física. Respondiendo al tercer objetivo específico, se definió la propuesta integradora que se orientó a determinar la orientación que requiere el docente responsable de la asignatura de educación física para mejorar su desempeño en la aplicación de juegos en contribución al desarrollo de la motricidad gruesa. durante las clases de educación física con estudiantes de educación básica elemental de cuarto grado de la escuela de educación básica Paul Harris como aporte para el mejoramiento de la motricidad gruesa. La propuesta estuvo compuesta de cuatro fases de implementación dirigidas a una directora y docente de aula además se incluyó los recursos logísticos y la valoración de la factibilidad con las dimensiones, técnica, económica, social y ambiental, demostrando la capacidad para lograr los objetivos de la propuesta, determinando la viabilidad y capacidades materiales con los que cuentan las partes ejecutoras de la propuesta.
Keywords: JUEGO LUDICO; MOTRICIDAD; COORDINACION; ESTRATEGIA METODOLOGICA